Assessment of Sea Water Quality in some Limestone Island and Archipelagos areas, Viet Nam - Trang, Cao Thi Thu; Thung, Do Cong; Nam, Le Van; Kha, Pham Thi; Bach, Nguyen Van; Ngoc, Dinh Hai (VNU Journal of Science: Earth and Environmental Sciences; Vol 36 No 1DO - 10.25073/2588-1094/vnuees.4556, 2020)
With nearly 3,000 large and small islands, the islands and archipelagos of Vietnam have outstanding features in terms biodiversity and geology. The islands are mainly formed from carbonate (limestone), intrusive igneous rock, sedimentary and volcanic rocks, in which limestone islands predominate, distributed mainly in the Gulf of Tonkin. This paper presents the results of researches and assessments on sea water quality of Vietnam's typical limestone islands and archipelagoes through the 2017-2018 surveys. The research results show that although the water quality around of limestone and archipelago area of Vietnam is safety for the development of aquatic life, an increase in pollutants concentration in water has been recorded when compared to previous research results. The research results supplement the data set of sea water quality in limestone areas that defining the characteristics of marine biodiversity. Keywords: limestone island, water quality, pollutants.